Strategies to design a program for cultivating holistic integrative pharmacy professionals - Mengdan XU; Laiyou WANG; Min SHI; Baohuan LEI (Journal of Holistic Integrative Pharmacy)
[Abstract]: After reviewing the advancements about “holistic integrative pharmacy” (HIP) and the goal of HIP education, we propose five strategies to design a program for cultivating HIP professionals. The following strategies are believed to offer a reference for domestic and foreign educational community counterparts to explore the suitable cultivation mode for HIP professionals. These strategies entail establishment of a multidisciplinary teaching team, reconstruction of teaching organization structure, design and integration of the curriculum system, construction of textbooks, and the shift of teaching and examination mode.